Menakar Mahar: Studi tentang Masyarakat Santri di Desa Karangbesuki Sukun, Kota Malang - Ahmad Izzuddin (Sabda: Jurnal Kajian Kebudayaan, 2019)
Islamic marriage rules in practice form values that are lived out and practiced in the context of cultural society so that they emerge as symbols as a form of the dialectical process between religious values and cultural values. As an example of the concept of dowry in Islam which has two dimensions, the universality of the values adhered to by all its adherents and also the value locality that is formed from the dialectical process that occurs between religious teachings and the local culture of the adherents. This was seen in the santri community in Karangbesuki Village, Malang City in determining the dowry in their marriage by identifying aspects of the normative dowry in the fiqh that they embraced into their marital culture.